Talking With Your Child - Kate Fogarty; Evelyn Rooks-Weir; Millie Ferrer (EDIS)
Revised! FCS2006, a 2-page fact sheet by Kate Fogarty, Evelyn Rooks-Weir, and Millie Ferrer, provides guidance for parents in this very important part of quality parent-child relationships. This version is expanded from one to two pages, and adds color illustrations, additional research-based information on language acquisition throughout, and references. Published by the UF Department of Family Youth and Community Sciences, June 2006.